Theorizing Feminist Ethics of Care in Early Childhood Practice Possibilities and Dangers - Langford, Rachel (Feminist Thought in Childhood Research, 2019)
This open access book responds to a growing academic interest in theorizing care and care work in the early childhood education and care (ECEC) sector. The contributors theorize a new feminist ethics of care in everyday early childhood practice, revealing its complexities and importance. Drawing on feminist theories and philosophies, the chapter authors show how the caring practices of early childhood educators involve values, emotions, decision-making, action and work. Using cutting-edge theory, authors address the social locations and the inclusion and exclusion of both care givers and care receivers. With contributions from Belgium, Canada, New Zealand, the UK and the USA, the volume brings together early childhood studies, sociology, psychology, philosophy and critical disability studies to offer diverse perspectives on feminist ethics of care in early childhood practice and its possibilities and dangers. The ebook editions of this book are available open access under a CC BY-NC-ND 3.0 licence on bloomsburycollections.com.